Chlamydia caviae infection alters abundance but not composition of the guinea pig vaginal microbiota - Neuendorf, Elizabeth (Pathog Dis, 2015)
In humans, the vaginal microbiota is thought to be the first line of defense again pathogens including Chlamydia trachomatis. The guinea pig has been extensively used as a model to study chlamydial infection because it shares anatomical and physiological similarities with humans, such as a squamous vaginal epithelium as well as some of the long-term outcomes caused by chlamydial infection. In this study, we aimed to evaluate the guinea pig-C. caviae model of genital infection as a surrogate for studying the role of the vaginal microbiota in the early steps of C. trachomatis infection in humans. We used culture-independent molecular methods to characterize the relative and absolute abundance of bacterial phylotypes in the guinea pig vaginal microbiota in animals non-infected, mock-infected or infected by C. caviae. We showed that the guinea pig and human vaginal microbiotas are of different bacterial composition and abundance. Chlamydia caviae infection had a profound effect on the absolute abundance of bacterial phylotypes but not on the composition of the guinea pig vaginal microbiota. Our findings compromise the validity of the guinea pig-C. caviae model to study the role of the vaginal microbiota during the early steps of sexually transmitted infection.